Female EFL Pre-Service Teachers’ Experiences During Field Teaching Practice at Vocational School - Nurfaidah, Sitti; Ramadhani, Aulia; Malaka, Sartina (AL LUGHAWIYAAT, 2023)
In the context of teacher training, the integration of gender dynamics within the educational setting has received increasing attention, particularly in environments where gender roles are distinctly emphasized. However, there remains a significant gap in the literature concerning the specific challenges and strategies of female EFL pre-service teachers in male-dominated vocational schools, which this study seeks to explore. This qualitative study aims to uncover the experiences of female EFL pre-service teachers during their field teaching practice in a male-dominated vocational school. The data were gathered from the reflections of nine female pre-service teachers. The findings revealed a variety of experiences encountered by the participants. They shared their initial reactions and feelings upon being assigned to teach at the school, the challenges they faced during the teaching practice, the difficulties encountered when interacting with male students, and the strategies they developed to overcome these interaction challenges.Keywords: Female EFL pre-service; field teaching practice; vocational school